PENERAPAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN MEMBACA DONGENG PADA SISWA KELAS 3 SDN BUKUR 2 - Cerianing Putri Pratiwi (BAHASTRA, 2018)
The purpose of this research is (1) to describe the application of character education in the planning of learning to read fairy tales (2) to describe the application of character education in the implementation of learning to read fairy tales (3) to describe the application of character education in the learning of fairy tale reading in grade 3 students. This research is a qualitative research descriptive. In this study the data collected in the form of facts and information on the application of character education in learning to read fairy tales in grade 3 elementary school students. In this study the data source is teachers and students. Data collection techniques used in this study consist of (a) documentation, (b) observation, (c) interviews, and (c) tests. Data analysis technique is done by using interactive data model analysis technique. The result of the research shows that in the learning of reading fairy tales in grade 3 elementary school students in the planning stage, implementation stage, and assessment phase have integrated character education value. The values of character education found in the values of religious, responsibility, hard work, self-confidence, creative thinking, independent, courteous, curiosity, discipline.